Sinergity of Ethical Aspects and State Defense Characters to Accounting Competency - G. S. Budiwitjaksono; Indrawati Yuhertiana; Luqita Romaisyah (Future Science)
The aim of this study is to explain empirically about the synergy of ethical aspects, the character of state defense and accounting competence in the accounting profession society. This study is a development of the results of Gideon's research (2018), especially in the aspect of behavior. This study method uses qualitative research, with an interpretive approach with interview and observation data collection techniques in several accounting profession communities, especially accountants who work as public accountants, tax accountants, management accountants and educator accountants, in several cities in Java, including : Surabaya, Semarang, Yogyakarta, Bandung, Jakarta. The result of this study showed that accountants are professions that carry out their work always prioritizing aspects of controlled behavior based on a code of ethics regulated in his profession. And accountants also carry out their work in accordance with scientific abilities and technical expertise. Professional accountants show competence that requires several components, namely; special knowledge that demands continuous and consistent expertise or skills and experience; very high moral standards; serve the interests of the community; there is a special permit to run a profession; become a member of a profession. The character of Defending the country is a trait that shows a strong spirit that always grows and develops continuously in carrying out every professional activity. The synergy of the ethical component and character of the state defense can be the strength of the accountant's self in creating adequate competence, and can become a basic ability or need to form a professional individual.